Structural, elastic and optical properties of xSrO- 10PbO-(90-x)B₂O₃, xPbO-30SrO-(70- x) B₂O₃ and xSrO-(90-x) B₂O₃-2CeO₂- 8A1₂O₃ borate glasses in borate anomaly region / Nurul Syahidah Sabri - Sabri, Nurul Syahidah (2018)
Glass samples with the composition of xSrO-10PbO-(90-x) B₂O₃ (x = 20-45), xPbO- 30SrO-(70-x) B₂O₃ (x = 0-25) and xSrO-(90-x) B₂O₃-2CeO2-8Al₂O₃- (x = 25-50 mol%) were prepared by melt-quenching method to elucidate the structural, elastic and optical behavior in borate anomaly region. Characterization techniques like X-ray diffraction (XRD), Fourier transforms infra-red spectroscopy (FTIR), ultrasonic measurement, UV-Visible and Luminescence (for SrO- B₂O₃-Ce02-Al203) spectroscopes are employed in the present work. XRD data showed amorphous nature for SrO-PbO-B2C>3 samples while mixed crystalline/amorphous phases for the SrO B₂O₃- Ce02-Al203 samples at x > 35 mol%. FESEM image and EDX analysis revealed that the samples contained Ce-rich crystalline phase and Ce depleted glass phase. FTIR analysis revealed the presence of BO4 and BO3 vibration groups. Variation of SrO in SrO-PbO-B2C>3 and SrO- B₂O₃-Ce02-Al203 samples has resulted in increased ultrasonic velocities, elastic moduli (Cl,μ, K and Y), hardness (H), Debye temperature (0D) at lower SrO content but decreased for higher SrO addition. The increase in the elastic moduli indicates the increase of network rigidity of the glass system, related to the borate anomaly where the coordination number increased with the addition of SrO. At higher SrO additions in SrO-PbO-B203 samples, NBO formation resulted in decrease of elastic properties. Meanwhile, decrease in elastic moduli for SrO- B₂O₃- Ce02-AI₂O₃- samples related to the formation of NBO and grain/phase boundaries due to mixed crystalline/amorphous phases. The fraction of the four coordinated boron atoms (N4) values, calculated from FTIR spectra have same trend with elastic properties results. Quantitative analysis of ultrasonic data using the bulk compression and ring deformation models showed reduction in the ratio of calculated bulk modulus to the experimental bulk modulus, Kbc/Ke indicating decreased ring deformation in borate anomaly region…